2010
DOI: 10.4236/me.2010.12006
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low Cost Airlines Growth in Italy

Abstract: In recent years, low cost carriers (LCCs) have been the fastest growing sector of the aviation industry. The routes served by these carriers were undersized in comparison with principal routes, but deregulation made possible an efficient access to many new markets. The new generation of regional and low cost carriers have enabled a better matching of capacity to demand on routes previously served solely by large airlines, experiencing an increasing role in spatial development. Regional airports impact on local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Moreover through flying to relatively unknown destinations, it is claimed that LCCs have opened up new tourist markets. Indeed in a study related to Italy, Campisi, Costa, and Mancuso (2010) found that LCC services could have a favourable impact on economic development including increased tourism and the potential for cluster development. Elsewhere in Spain a survey of nearly 500 tourist establishment managers found that there was also a positive view of the role of the airport in economic development and in particularly those served by LCCs as opposed to network carriers (Castillo-Manzano et al, 2011).…”
Section: External Impactsmentioning
confidence: 98%
“…Moreover through flying to relatively unknown destinations, it is claimed that LCCs have opened up new tourist markets. Indeed in a study related to Italy, Campisi, Costa, and Mancuso (2010) found that LCC services could have a favourable impact on economic development including increased tourism and the potential for cluster development. Elsewhere in Spain a survey of nearly 500 tourist establishment managers found that there was also a positive view of the role of the airport in economic development and in particularly those served by LCCs as opposed to network carriers (Castillo-Manzano et al, 2011).…”
Section: External Impactsmentioning
confidence: 98%
“…In many cases, the statement is introduced as a reasonable hypothesis (e.g., Campisi et al, 2010;Forsyth, 2008;Duval, 2013;Fu et al, 2010) or as being obvious (e.g., Teles et al, 2009), without, however, appropriate supporting evidence. Increasing air traffic (flights, routes and passengers) is cited as evidence supporting such hypotheses, but without establishing a clear causality with tourist patterns, or even showing them.…”
Section: Assessing the Impacts Of Aviation Liberalisation On Tourism:mentioning
confidence: 99%
“…Selanjutnya riset menunjukkan bahwa transportasi moda udara mempunyai peranan dalam meningkatkan jumlah kunjungan wisatawan (Campisi et al, 2010;Forsyth, 2008;Duval, 2013;Fu et al, 2010 Adalah setiap pengunjung seperti definisi di atas yang tinggal kurang dari dua puluh empat jam di tempat yang dikunjungi (termasuk cruise passenger yaitu setiap pengunjung yang tiba di suatu negara dengan kapal atau kereta api, dimana mereka tidak menginap di akomodasi yang tersedia di negara tersebut).…”
Section: Gambar 1 Peringkat Kunjungan Wisman DI Wilayah Aseanunclassified